2012
DOI: 10.3139/146.110788
|View full text |Cite
|
Sign up to set email alerts
|

Severe tempering of bainite generated at low transformation temperatures

Abstract: The response of a strong bainitic-steel to tempering at high temperatures is investigated, because a softened state is sometimes necessary during the manufacture of engineering components, prior to the final heat-treatment which hardens the material. Thermodynamic calculations conducted to determine the maximum temperature at which the steel could be annealed without forming austenite were found to significantly overestimate the actual temperature at which austenite, ferrite and cementite (γ + α + θ) can coexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…Softening may also be necessary to allow thermo-mechanical processing. [10,11] Previous work has shown that these steels are relatively resilient to tempering. [1,8,12] The fine plate size provides the dominant strength contribution, so high hardness is maintained until coarsening of the bainitic ferrite occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Softening may also be necessary to allow thermo-mechanical processing. [10,11] Previous work has shown that these steels are relatively resilient to tempering. [1,8,12] The fine plate size provides the dominant strength contribution, so high hardness is maintained until coarsening of the bainitic ferrite occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The tempering treatment applied is sufficient in this alloy to remove the retained austenite but not sufficient to subsequently coarsen the ferrite, and previous work shows that coarsening occurs after the austenite has decomposed and is associated with a large drop in hardness. [21,25,26,32] These calculations support a correlation between the amount of hydrogen at saturation and the predicted grain boundary surface area per unit volume, rather than simply to the volume fraction of austenite (see Table III). As a result of the displacive transformation to carbide-free bainite, the grain boundaries will be predominantly of a single orientation relationship.…”
Section: Resultsmentioning
confidence: 83%
“…After saturation with hydrogen, 7 ppmw was desorbed by heating to 673 K, increasing to more than 9 ppmw after introducing micro-cracks by heat treatment; this suggests that incoherent phases can be used to introduce strong trapping sites. [32,33] In the evolution curves observed, the presence of austenite is associated with a shift in the desorption peak to around 498 K (225°C) from 383 K (110°C). At saturation, the diffusible hydrogen level was similar in the three conditions observed, with evolution curve similar below 383 K (110°C).…”
Section: Discussionmentioning
confidence: 94%
“…The as-transformed structure of Alloy 2, shown in figure 3a, is coarser, with an average plate thickness of 83 nm. Bainitic steels, such as the alloys studied here, are resistant to tempering, with little reduction in hardness or austenite volume fraction below 450 • C and significant softening only taking place at temperatures above 500 • C [27][28][29]. This is reflected in the fact that the hardness remains high in both alloys, even after tempering at 500 • C for 1 h. However, the reduction in hardness following the tempering treatments signals the onset of austenite decomposition, as confirmed by X-ray analysis (table 3).…”
Section: Results and Discussion (A) Transmission Electron Microscopicmentioning
confidence: 99%
“…Previous work on nanostructured bainite has shown that the decomposition occurs during isothermal heat treatment at temperatures of 400 • C or above [27,29,38,39]. However, these experiments involve continuous heating, so dilatometric experiments were done to measure the temperature range over which the substantive decomposition of austenite occurs.…”
Section: (F) Decomposition Of Retained Austenitementioning
confidence: 99%